Dinamika Praktek Ekonomi dan Perdagangan Pada Masa Daulah Bani Umayyah, Bani Abbasiyah dan Turki Utsmani - Khoir, Miftah; Hikmah Al Kholidah, Aufa (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2026)
This study examines the dynamics of economic and trade practices that developed during the three periods of Islamic caliphate, namely the Umayyad Caliphate (661-750 AD), the Abbasid Caliphate (750-1258 AD), and the Ottoman Empire (1299-1924 AD). Through the application of a qualitative approach with historical research methods, this study highlights the transformation of the economic system, covering aspects of monetary and fiscal policy, as well as trade networks in each period. The findings reveal continuity in the use of precious metal-based currencies and the application of sharia economic principles in the three caliphates. However, each period exhibits distinct economic characteristics: the Umayyad era was marked by administrative consolidation and currency standardization, the Abbasid period saw advancements in financial innovation and integration with global markets, while the Ottoman era was characterized by the implementation of a centralized command-based economic model. The differences in these economic management models were also influenced by political factors, technological developments, and the global context faced by each caliphate. Keywords: Islamic Economy, Trade, Umayyad Dynasty, Abbasid Dynasty, Ottoman Empire, Economic History, Dynasty Comparison.